(untitled) (Vietnam Journal of Community Medicine, 2022)
The SARS-CoV-2 virus strain has caused a pandemic in the world since 2019 with its increasing ability to spread with new mutations. We report that a 19-day-old newborn is the youngest case recorded at Duc Giang General Hospital and Hanoi at the moment. The child is a horizontal transmission of Covid-19 infection, diagnosed by PCR of positive nasopharyngeal fluid. Children are classified as severe pneumonia due to Covid-19 with symptoms: fever, gastrointestinal, respiratory symptoms, inflammatory markers, and very high D-dimer. The child was treated with respiratory support with oxygen, corticosteroids, anticoagulants, antibiotics, and nutritional care. The child stopped treatment after 12 days and was discharged after 21 days with his family.